2016
DOI: 10.1055/s-0042-108190
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic evaluation of celiac disease severity and its correlation with histopathological aspects of the duodenal mucosa

Abstract: Background and study aims: Celiac disease (CD) is a chronic systemic autoimmune disorder affecting genetically predisposed individuals, triggered and maintained by the ingestion of gluten. Triggered and maintained by the ingestion of gluten, celiac disease is a chronic systemic autoimmune disorder affecting genetically predisposed individuals. Persistent related inflammation of the duodenal mucosa causes atrophy architecture detectable on esophagogastroduodenoscopy (EGD) and histopathology. We investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
2
0
1
Order By: Relevance
“…This is in contrast by observations made by Bonatto MW et al and Dickey W who had concluded in their studies that the changes in the duodenal mucosa were significantly and positively associated with histopathologic findings. 18,19 Our findings are similar to those conducted by Kazi JI et al 14 who have also concluded similar results as in the present study of poor predictive value of endoscopy alone in comparison to histopathological examination.…”
Section: Duodenal Lesionssupporting
confidence: 93%
“…This is in contrast by observations made by Bonatto MW et al and Dickey W who had concluded in their studies that the changes in the duodenal mucosa were significantly and positively associated with histopathologic findings. 18,19 Our findings are similar to those conducted by Kazi JI et al 14 who have also concluded similar results as in the present study of poor predictive value of endoscopy alone in comparison to histopathological examination.…”
Section: Duodenal Lesionssupporting
confidence: 93%
“…The authors showed that this classification increased the agreement between endoscopy and histopathology. However, the agreement remained weak in less severe cases ( 38 ).…”
Section: Discussionmentioning
confidence: 96%
“…Notre patient présente une forme de MC sèche sans troubles du transit et le diagnostic a été porté sur la fibroscopie digestive haute. Les avancées dans les méthodes de diagnostics et de dépistage ont contribué à une augmentation apparente de l’incidence des MC puisque plus de 80 % des cas diagnostiqués sont asymptomatiques ou pauci symptomatiques [ 4 ]. Sa sérologie était négative et on estime qu’elle n’est utile que dans 58%; 44,8% et 36,8% respectivement pour les anticorps anti gliadine de type A, les anti endomysium et les anti transglutaminases [ 5 ].…”
Section: Discussionunclassified